Debt Management in the Polish Self-Government Theoretical and Pragmatic Aspects - Krasucka, Maja (Zarządzanie długiem w polskim samorządzie - aspekty teoretyczne i pragmatyczne, 2010)
The article presents the problems of self-government debt management, its notion and scope. Moreover, the paper shows legal limitations of taking debt in Poland in comparison with the European Union countries. In its next part it characterizes the level and structure of Polish self-governments debt between 2004 and 2008, and presents the conclusions concerning the assessment of standards realized by SGE in scope of debt management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 95-108
Keywords: public debt; self-government; debt management; debt limit; the structure of debt